QRIS DALAM PERSPEKTIF FIQIH MUAMALAH: STUDI ATAS KEABSAHAN DAN AKAD DALAM PEMBAYARAN NONTUNAI - Lanifa Fauzia Comersyah; Sabrina Oktavia Ramadani; Alyasa Najwa (Media Riset Bisnis Manajemen Akuntansi, 2025)
This study discusses the use of the Quick Response Code Indonesian Standard (QRIS) as a cashless digital payment tool from the perspective of Islamic commercial jurisprudence (fiqh muamalah). QRIS is an electronic payment system recognized by Bank Indonesia to facilitate non-cash transactions in the country. From an Islamic legal standpoint, it is essential to analyze the validity of transactions and the underlying akad (contracts), as sharia principles require clarity (bayyinah), mutual consent (ridha), and the lack of riba (usury), gharar (uncertainty), and maisir (gambling). This research adopts a descriptive quantitative approach and literature study method to examine QRIS in the context of fiqh muamalah, particularly focusing on the validity and contracts involved in non-cash payments. The findings of this study indicate that the use of QRIS in financial transactions can be considered valid under Islamic law, provided it fulfills the essential elements and conditions of a valid contract, such as price clarity, transaction object, and mutual consent.Keywords : QRIS, Fiqh Muamalah, Non-Cash Transaction, Akad Islamic Economics